Service API Modeling and Comparison: A Technology-Independent Approach - Vales, Zdenek; Brada, Premek (2020 46th Euromicro Conference on Software Engineering and Advanced Applications (SEAA), 2020)
When service-based applications are used in systems where context varies in time or location (mobile, adaptive systems), clients may need to switch service providers for various reasons like temporary outage or geographical relocation. To prevent negative impacts on overall functionality, both the client and the provider need a way of discovering whether the application programming interface (API) of an alternative web service is compatible with client's expected contract. However, the diversity of API specification technologies poses a challenge in such evaluation. Building on previous results, in this paper we present a general model of (web) service APIs, a method for creating corresponding service API representations for several technologies, and a method for comparing these representations to evaluate API compatibility from client's point of view. Both the model and the comparison method have been implemented and verified on real-world services.